Complex, intelligent, and software intensive systems : proceedings of the 11th International Conference on Complex, Intelligent, and Software Intensive Systems (CISIS-2017) /: proceedings of the 11th International Conference on Complex, Intelligent, and Software Intensive Systems (CISIS-2017). ([2018]) - Unknown
No abstract available